Guidelines for the diagnosis and treatment of cholangiocarcinoma: an update. Issue 12 (15th August 2012) - Khan, Shahid A; Davidson, Brian R; Goldin, Robert D; Heaton, Nigel; Karani, John; Pereira, Stephen P; Rosenberg, William M C; Tait, Paul; Taylor-Robinson, Simon D; Thillainayagam, Andrew V; Thomas, Howard C; Wasan, Harpreet
Abstract : The British Society of Gastroenterology guidelines on the management of cholangiocarcinoma were originally published in 2002. This is the first update since then and is based on a comprehensive review of the recent literature, including data from randomised controlled trials, systematic reviews, meta-analyses, cohort, prospective and retrospective studies.